Dad bakes - Yamasaki, Katie (Norton Young Readers, 2021)
Dad rises before the sun, goes to work at the bakery where he kneads, rolls, and bakes bread, and as the world starts its day, Dad heads home to his young daughter where they play, read, and bake together.